SADIQ and the Desert Star - Nuurali, Siman; Sarkar, Anjan (North Mankato, Minnesota : PICTURE WINDOW BOOKS, 2020)
When Sadiq's father leaves on a business trip, he worries he'll miss his baba too much. But Baba has a story for Sadiq: the story of the Desert Star. Learning about Baba's passion for the stars sparks Sadiq's interest in outer space. But can Sadiq find others who are willing to help him start the space club of his dreams?
Keywords: Sadiq -- (Fictitious character) -- Juvenile fiction; Planetariums -- Juvenile fiction; Children of immigrants -- Juvenile fiction; Friendship -- Juvenile fiction; American fiction; Africans -- United States -- Juvenile fiction; Children's stories